Rubens unveiled : paintings from lost Antwerp churches - Herremans, Valérie (Rubens unveiled, 2013)
This is the second volume in the series Rubens Unveiled, in which the Rubens Research Project of the Royal Museum of Fine Arts Antwerp shares the fruits of its research with a wider public. It follows a first book on Rubens' painting technique. This second publication explores the physical, spiritual and cultural context of several major Rubens paintings in the Antwerp museums collection, drawn from four once-prominent houses of worship in the city. The Norbertine Abbey of St Michael, the Franciscan Church, and the churches of the Calced and the Discalced Carmelites were all suppressed during the French occupation that began in 1794. The book describes the history of these religious institutions and reveals how they looked, inside and out